Treatment of domestic cats with pancreatitis - Dereza, Yu. (Scientific Progress & Innovations, 2025)
The treatment of domestic cats with pancreatitis is complicated. Most cases of the disease have recurrences, and therefore, the therapeutic regimen should be aimed at relieving pain, inflammation, intoxication, eliminating further progression of the disease, eliminating clinical signs, and improving the quality of life of the animal. The article emphasizes the importance of an integrated approach to treating cats with pancreatitis. The aim of the study was to analyze the effectiveness of treatment regimens for domestic cats in case of pancreatic inflammation. According to studies, 87.5 % of cats with and suspected of having pancreatitis had appetite disorders (ano-/hyporexia), dehydration (83 %), vomiting (75 %), and pain (65 %). Ultrasonography in such animals visualized hypoechoic thickening of the pancreas with a surrounding hyperechoic layer, indicating inflammatory process. In the blood serum of patients and suspected pancreatitis cats, an increase in the level of glucose (GLU) by 45.6 and 62.6 % (P<0.001) was recorded compared to clinically healthy animals, an increase in amylase activity (AMY) by 39.0 and 2.3 % (P<0,001) compared to the upper limit of physiological fluctuations, and the activity of pancreatic lipase (fPLI) by 2.2 and 1.6 times (P<0.001) compared to clinically healthy animals, which confirms the violation of functional state of the pancreas of animals. The use of complex treatment of cats with pancreatitis for 14 days helped to improve appetite, disappearance of pain and signs of dehydration. Hematological parameters of animals of both experimental groups improved, glucose level (GLU) (Р<0.001), amylase activity (AMY) of the first (Р<0.01) and second groups (Р<0.001), pancreatic lipase activity (fPLI) of the first group (Р<0.01) decreased. In order to support the body of cats with pancreatitis, it is necessary to control pain and adhere to a lifelong diet.